Theoretical and legal perspective on the content of the objectivity of Article 178 of the Ukrainian Code of Administrative Offences: thesis, antithesis, arguments, presentation - K. O. Chyshko (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The article is structured according to the elements of the logical operation of “proof”, which includes the following elements.